Design Aplikasi “Hadis-Hadis Sains” Melalui Website Kodular - Nadya Silvy (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Science and technology became something that developed very rapidly in the classical period and Islamic civilization. And this proves that epistemology developed at that time. Even though in the past Muslim scholars studied a lot in the field of Islamic civilization, with their epistemology they were able to provide the best in the field of science and technology and develop it to all corners of the world. Technology is a source of information today. It is necessary to know that the hadiths of the Prophet Muhammad contain many Hadiths about Science and Technology. What is contained in the hadith is mentioned implicitly in the rules of explanation of creed and faith. That is why, hadith will always coexist with the development of the times and there will be no conflict between the two forever. The